The Inclusion of Ideology in Jokowi’s Speech Viewed from the Perspective of Appraisal Theory - Listiani, Gisty; Rukmini, Dwi; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2019)
Ideology is a belief towards a particular idea which is commonsensical as it is required by the society as the answer of particular issues. In common practices, ideology might become considerable since it is realised through the use of words that are meaningful and powerful. One language feature that can be used to convey ideology is appraisal resources. This research aimed to describe the inclusion of ideology viewed from the perspective of appraisal theory. It employed descriptive qualitative approach. The object of the study is a speech text performed by Jokowi in the World Economic Forum of Asean 2018. The results of the study depicted that there were seven ideology strategies that had been implemented viewed from the attitude appraisal analysis. The seven ideologies were implication, consensus, hyperbole, pre-supposition, national self glorification, lexicalization, and irony. Besides, the ideology inclusion in Jokowi’s speech viewed from the perspective of engagement appraisal pointed that there were six ideology strategies that were implemented by the speaker. They are implication, evidentially, pre-supposition, national self glorification, hyperbole, vagueness, and consensus. In addition, the inclusion of ideology in Jokowi’s speech viewed from the perspective of graduation appraisal conveyed that there were four ideologies applied in the speech, they were implication, hyperbole, national self glorification, and number game. By taking account of the results, this study is expected to escalate the quality of English teaching and learning dealing with words understanding beyond the meaning.